Tropical forest canopies and their relationships with climate and disturbance: results from a global dataset of consistent field-based measurements - Pfeifer, M.; Gonsamo, A.; Woodgate, W.; Cayuela, L.; Marshall, A.R.; Ledo, A.; Paine, T.C.E.; Marchant, R.; Burt, A.; Calders, K.; Courtney-Mustaphi, C.; Cuní-Sanchez, A.; et al. (Elsevier, 2018)
Background Canopy structure, defined by leaf area index (LAI), fractional vegetation cover (FCover) and fraction of absorbed photosynthetically active radiation (fAPAR), regulates a wide range of forest functions and ecosystem services. Spatially consistent field-measurements of canopy structure are however lacking, particularly for the tropics.